The role of corneal hysteresis during the evaluation of patients with possible normal-tension glaucoma - Chen M (Dove Medical Press, 2018)
Ming Chen,1 Laura Kueny,2 Arthur L Schwartz2 1Department of Surgery, Division of Ophthalmology, University of Hawaii, Honolulu, HI, USA; 2Department of Ophthalmology, Georgetown University, Washington, DC, USA Purpose: There are multiple reports of the role of corneal hysteresis (CH) as an independent risk factor for the diagnosis and risk of progression of normal-tension glaucoma (NTG). Our study measured CH with the Ocular Response Analyzer (ORA) in patients with intraocular pressure (IOP) <21 mmHg to investigate if a low CH would identify NTG in this Asian-based practice. Methods: This was a prospective cross-sectional study of patients who underwent routine eye examination during 2016 in a private practice in Honolulu, Hawaii, where most patients are Asian. Inclusion criteria are: 1) ≥65 years 2) IOP <21 (compensated IOP by ORA), and 3) CH values <10 using ORA as measured by a single experienced technician. Exclusion criteria are: 1) sight-limiting ocular or corneal disease that would preclude accurate measurements for the purposes of the study. 2) Any patient who had difficulty in being tested with the ORA. 3) Patients who had any history of any type of glaucoma. All patients that met the inclusion criteria underwent fundus photography to measure cup-to-disc ratio and cup-to-disc asymmetry and also had central corneal thickness measured. Thickness of the retina nerve fiber layer was measured by ocular coherence tomography. The eyes with an average retina nerve fiber layer thickness less than 80 µm were classified as possible NTG and were scheduled for a visual field test. The field examination was considered valid only if the fixation, false positives, and false negatives were within the acceptable range. Patient demographics and data on preexisting diseases were collected including age, sex, coexisting medical conditions, and previous intraocular surgery. Those with thinning of retina nerve fiber layer on optical coherence tomography had a Humphrey visual field test to confirm the diagnosis of glaucoma. Results: Seventy-six eyes of 46 patients that met the eligibility criteria were included in the study. Twenty-one previously undiagnosed eyes were confirmed as having NTG, which corresponds to an incidence of 27.6%. Conclusion: CH measurement is a valuable test to assist in early diagnosis of NTG, especially in the elderly Asian population. With an established diagnosis, aggressive early treatments medically or surgically to further lower IOP can prevent irreversible blindness, which can severely impact the patient’s family and socioeconomic status. Keywords: glaucoma, normal-tension glaucoma, intraocular pressure, corneal hysteresis, Ocular Response Analyzer